Evaluating the Human Disturbance to Karst Environments in Southern Italy - Calò, Fabiana; Parise, Mario (Acta Carsologica, 2006)
Karst environments are extremely vulnerable to degradation and pollution. Although the carrying capacity of these natural environments is low, a variety of human activities is implemented on karst settings generating impacts at the surface and subsurface. To evaluate the degree of disturbance to typical karst environments in the Mediterranean basin, two areas have been selected in Apulia (south-eastern Italy). The human-induced effects are being assessed by applying a recently developed Karst Disturbance Index (KDI), based on a categorical framework encompassing physical, biological, and social aspects, and the evaluation of a number of indicators for each category. Scores are assigned to the indicators, to assess the severity and the extent of the human impacts on the karst environment. Knowledge of the study areas derives from a combined use of direct experience and field surveys, and the critical evaluation of data available from research articles and local organization reports. Since this approach is an holistic and comprehensive method, different scientific branches and law issues have been considered. The results so far obtained for the study areas highlight the urgent need of a sustainable management of anthropogenic activities: for example, quarrying and stone clearing, both extensively widespread, are among the most dangerous practices for karst surface and subsurface landforms in Apulia. These activities are heavily changing the original karst landscape and causing the partial or total destruction of natural caves. This study represents a preliminary evaluation of the human disturbance to karst in Apulia, but has to be necessarily integrated by further applications in other areas of the region, aimed at a better understanding of the potentiality of the approach and its feasibility in different karst settings.